2022
DOI: 10.3390/ijms23158540
|View full text |Cite
|
Sign up to set email alerts
|

Atom Transfer Radical Polymerization of Pyrrole-Bearing Methacrylate for Production of Carbonyl Iron Particles with Conducting Shell for Enhanced Electromagnetic Shielding

Abstract: The conducting polymer poly(2-(1H-pyrrole-1-yl)ethyl methacrylate (PPEMA) was synthesized by conventional atom transfer radical polymerization for the first time from free as well as surface-bonded alkyl bromide initiator. When grafted from the surface of carbonyl iron (CI) a substantial conducting shell on the magnetic core was obtained. Synthesis of the monomer as well as its polymer was confirmed using proton spectrum nuclear magnetic resonance (1H NMR). Polymers with various molar masses and low dispersity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This structure provides a well-defined conductive path and controllable conductivity–temperature characteristics for optimizing dielectric losses as well as delaying the attenuation of magnetic losses at high temperatures. Mrlík et al [ 21 ] prepared a conducting polymer, namely poly(2-(1H-pyrrole-1-yl)ethyl methacrylate, and obtained a substantial conducting shell on the magnetic core when grafted from the surface of carbonyl iron. Shen et al [ 22 ] confirmed that CIP–calcium particles with core–shell structures formed during the hydration of the composites without fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…This structure provides a well-defined conductive path and controllable conductivity–temperature characteristics for optimizing dielectric losses as well as delaying the attenuation of magnetic losses at high temperatures. Mrlík et al [ 21 ] prepared a conducting polymer, namely poly(2-(1H-pyrrole-1-yl)ethyl methacrylate, and obtained a substantial conducting shell on the magnetic core when grafted from the surface of carbonyl iron. Shen et al [ 22 ] confirmed that CIP–calcium particles with core–shell structures formed during the hydration of the composites without fly ash.…”
Section: Introductionmentioning
confidence: 99%